Microstructure Effects of the Electrical Discharge Machining Drill on Aerospace Super Alloys - Garner Copher; Sandip Harimkar; Kurt Rouser; Connor McCain; Daniel Velasco; Tanner Price; Trey Schinzler (Advances in Materials Science and Engineering, 2022)
This paper presents an analysis of the parent material damage and electrode wear of a handheld electrical discharge machining (EDM) drill. The motivation of this study is to investigate the material effects of EDM drilling on aerospace alloys at a microstructure level. The specific effects that are being investigated are heat affected zones (HAZ), grain structure changes, material composition changes, and fracturing. A secondary goal of this study is to determine if there is potential for electrode wear prediction models for supply chain management. The study consisted of making cuts into both Inconel and titanium test specimens while varying cut depths and electrode diameters. The results of the study found that the electrode wear while cutting Inconel showed some amount of predictable behavior. On the contrary, the titanium specimens did not indicate a predictable behavior and did not appear to follow an intuitive trend. Interestingly, when drilling into titanium, the active electrode increased in length, indicating that the titanium is being deposited onto the electrode. The EDM drill caused notable damage to the parent material, including a substantial recast layer of up to approximately 150 μm in thickness, incorporation of electrode material into the parent material through the recast layer, and formation of microcracks that can cross the recast layer/parent material interface. These noted characteristics can have an impact on material performance and longevity due to the nonuniform nature of the damage and the introduction of microcracks crossing from the recast layer into the parent material.